(untitled) (Research, Society and Development, 2021)
The development of consistent information on the production of forensic exams is essential for the diagnosis and strategic planning of official forensic investigation units. The objective of this work was to outline some methodological strategies for the use of data produced by the forensic investigation units. Through a time series we sought to highlight the bottlenecks that hinder data consolidation. On the other hand, it was intended to point out ways for the construction of indicators that allow the adequate allocation of human and material resources and the integrated analysis of the police investigation with the work of the forensic scientists. The time series of requests for expert examinations were analyzed, as well as the types of exams carried out by the criminal and medical forensic units of the state of Rio de Janeiro from July 2013 to July 2016. These data were compared with official state criminal data. The results indicate the need to adjust the spatial organization of the forensic investigation units in line with the organization established for the other public security units in Rio de Janeiro. In addition, very different spatial and temporal dynamics were observed for the forensic investigations units and between the forensic medical unit and the criminal expertise unit. It was also noted the need to use crime data generated by the police stations to understand the demand for forensic investigations units.